Volume 8A: Ocean Engineering 2014
DOI: 10.1115/omae2014-23638
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Damping Effects on Heading Stability of Turret-Moored Ships

Abstract: Tankers used for offshore oil production and storage are kept in station by turret mooring systems, enabling the vessels to weathervane in the direction of the dominant environmental loads. These passive weathervaning systems have been observed in model experiments to be ineffective in swell-dominated long wave conditions. Over a range of wavelengths from 0.6 < λ/L < 2 (L – ship length), the vessel was observed to lose heading control in head sea condition, due to a pitchfork bifurcation that is initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In relation to multidegree of freedom motion, in Reference [14], the heading stability of a turret-moored ship was assessed by varying damping in different modes of motion. The study showed that viscous effects in pitch mode are stronger than heave or roll.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to multidegree of freedom motion, in Reference [14], the heading stability of a turret-moored ship was assessed by varying damping in different modes of motion. The study showed that viscous effects in pitch mode are stronger than heave or roll.…”
Section: Introductionmentioning
confidence: 99%